A dynamic chiral responsive luminescent conjugated polymer and a composite material thereof, preparation and application
By designing a composite material of a dynamic chiral responsive luminescent conjugated polymer and gold nanoparticles, the problems of existing materials in achieving both high glume and high ΦPL and insufficient dynamic responsiveness are solved. This results in highly efficient circularly polarized luminescence performance and dynamic control, expanding applications such as intelligent sensing and anti-counterfeiting encryption.
Patent Information
- Application Number
- CN202611204781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-11-06
AI Technical Summary
Existing polymer-based circularly polarized light-emitting materials struggle to balance high luminescence asymmetry factor and high luminescence quantum efficiency, and lack dynamic response modulation capabilities.
By designing a dynamic chiral responsive luminescent conjugated polymer, a polyphenylene diethyne backbone is covalently linked to chiral amino acid side groups. Combined with the localized surface plasmon resonance effect of gold nanoparticles, a composite material is prepared using electrostatic self-assembly technology to achieve a balance between high glume and high ΦPL, and dynamic regulation can be achieved through external stimulation.
Achieving a balance between high luminescence asymmetry factor and high luminescence quantum efficiency within the same system, and possessing dynamic response capability, broadens its application potential in fields such as information encryption storage, three-dimensional display, and chiral sensing.
Smart Images

Figure CN123042289A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chiral optics technology, and more specifically, relates to a dynamic chiral responsive luminescent conjugated polymer and its composite materials, preparation methods and applications. Background Technology
[0002] In recent years, circularly polarized luminescence (CPL) materials have shown great promise in fields such as information encryption and storage, three-dimensional displays, optoelectronic devices, and chiral sensing due to their unique chiral optical properties. Compared with inorganic or small-molecule CPL materials, polymer-constructed CPL materials exhibit larger transition dipole moments, better solution processability, and higher luminescence quantum efficiency. Φ PL With its outstanding advantages, chiral optical materials have become a research focus in the field of chiral optical materials. Among them, dynamic helical conjugated polymers not only have intrinsic chiral centers and conjugated luminescent backbones, but can also undergo reversible helical inversion under external stimuli, showing unique advantages in constructing smart chiral functional materials.
[0003] However, the luminescence asymmetry factor (g) of existing polymer-based CPL materials lum Smaller (usually 10) -4 ~10 -3 This severely restricts its practical application. To improve g lum Traditional methods often employ self-assembly strategies to amplify chirality, but this often leads to aggregation-induced emission quenching (ACQ) effects, resulting in a significant decrease in the luminescence quantum efficiency of the material.
[0004] Recent studies have shown that the localized surface plasmon resonance (LSPR) effect of noble metal nanoparticles can significantly enhance the luminescence performance of neighboring fluorescent materials. Among them, gold nanoparticles (AuNPs) are widely used due to their excellent LSPR effect, good biocompatibility, and size tunability. When fluorescent molecules are at an appropriate distance from the surface of gold nanoparticles, their excitation rate and radiative decay rate are significantly enhanced by the plasmon field, thus effectively compensating for the luminescence efficiency loss caused by self-assembly. Although combining chiral conjugated polymers with gold nanoparticles theoretically provides a new approach for constructing high-performance CPL materials, in practical preparation, the controllable grafting of polymers onto the nanoparticle surface remains challenging, and existing composite systems are mostly static structures lacking dynamic response control capabilities.
[0005] In summary, the existing technology has the following main shortcomings: polymer-based CPL materials are difficult to simultaneously achieve high g / L in a single system. lum With Gao Φ PLTraditional self-assembly chiral amplification strategies often come at the cost of sacrificing luminescence efficiency. Although composite systems of chiral conjugated polymers and gold nanoparticles have the potential for synergistic enhancement, the methods for orderly assembly of polymer ligands and gold nanoparticles are still immature, lacking simple, efficient and controllable preparation strategies. Moreover, most existing composite systems are static structures, lacking dynamic response to external stimuli and the ability to modulate chiral optical signals.
[0006] Therefore, there is an urgent need to develop a novel chiral luminescent material that combines high luminescence asymmetry factor and high luminescence quantum efficiency with dynamic stimulus response, in order to break through the performance bottleneck of existing CPL materials and broaden its application scenarios in optoelectronic devices such as intelligent sensing and anti-counterfeiting encryption. Summary of the Invention
[0007] To address the above-mentioned deficiencies or improvement needs of existing technologies, this invention provides a dynamic chiral responsive luminescent conjugated polymer and its composite materials, preparation method, and application, aiming to solve the technical problem that existing polymer-based circularly polarized luminescent materials are unable to simultaneously achieve high luminescence asymmetry factor and high luminescence quantum efficiency, and have insufficient dynamic response control capability.
[0008] To achieve the above objectives, in a first aspect of the present invention, a dynamically chiral responsive luminescent conjugated polymer is provided. The repeating unit structure of the polymer is shown in Formula 1, the main chain is a polyphenylene diacetylene folded structure, the main chain has a helical conformation in aqueous solution, and the side chains contain chiral amino acid units. In Formula 1, the R group represents the side chain residue of the chiral amino acid unit, and C... It is an L-type or D-type chiral carbon; Equation 1.
[0009] Preferably, R is one of methyl, isopropyl, isobutyl, sec-butyl, or benzyl.
[0010] Preferably, the polymer has a number-average molecular weight of 3,000 to 50,000 and a molecular weight distribution of 1.1 to 2.0.
[0011] In a second aspect of the present invention, a method for preparing a dynamically chiral responsive luminescent conjugated polymer as described in any of the first aspects above is provided, comprising the following steps: (1) Amidation reaction of chiral amino acid esters with 3,5-diiodobenzoic acid was carried out in an organic solvent in the presence of an acid-binding agent and a condensing agent to obtain chiral monomer benzyl(3,5-diiodobenzoyl)-amino acid esters. (2) Under the protection of an inert gas, using palladium catalyst and copper salt as catalysts, the chiral monomer benzyl(3,5-diiodobenzoyl)-amino acid ester obtained in step (1) is polymerized with m-diethynylbenzene via Sonogashira coupling reaction to obtain a polymer intermediate. (3) The polymer intermediate obtained in step (2) is hydrolyzed to remove the benzyl protecting group, and a dynamic chiral responsive luminescent conjugated polymer is obtained.
[0012] Preferably, in step (1), the chiral amino acid ester compound is a benzyl ester hydrochloride prepared from one of the following chiral amino acids: L-alanine, D-alanine, L-leucine, D-leucine, L-isoleucine, D-isoleucine, L-valine, D-valine, L-phenylalanine, D-phenylalanine; the acid-binding agent is triethylamine; the condensing agent is 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM); the organic solvent is tetrahydrofuran; the reaction temperature is 15℃~35℃, and the reaction time is 12h~48h; In step (2), the palladium catalyst is tetrakis(triphenylphosphine)palladium; the copper salt is cuprous iodide; the polymerization reaction is carried out in a mixture of organic solvent and triethylamine, the reaction temperature is room temperature, and the reaction time is 24h to 72h. In step (3), the hydrolysis is alkaline hydrolysis, and the alkali used is sodium hydroxide or potassium hydroxide; the hydrolysis reaction is carried out in a mixed system of organic solvent and water, and the hydrolysis is purified by dialysis.
[0013] In a third aspect of the invention, a dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material is provided, comprising the conjugated polymer described in any one of the first aspects above and gold nanoparticles, wherein the polymer and gold nanoparticles are composited through electrostatic adsorption.
[0014] Preferably, the mass ratio of the polyphenylene diacetylene folded body to the gold nanoparticles is 0.06:1 to 5.08:1; the mass ratio of the conjugated polymer to the gold nanoparticles is 0.06:1 to 5.08:1; the particle size of the gold nanoparticles is 5 nm to 100 nm; the surface of the gold nanoparticles is modified with a cationic surfactant, wherein the cationic surfactant is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.
[0015] In a fourth aspect of the present invention, a method for preparing a dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material as described in the third aspect above is provided, comprising the following steps: The polyphenylene diacetylene folded body was dissolved in ultrapure water to prepare a polymer solution, which was then mixed with a gold nanoparticle dispersion with a positively charged surface in a certain proportion. The polymer chain segments were grafted onto the surface of the gold nanoparticles by utilizing the electrostatic adsorption between the negative charge on the polymer surface and the positive charge on the surface of the gold nanoparticles. After centrifugation, washing and drying, the dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material was obtained.
[0016] Preferably, the mixing temperature is 10℃~40℃ and the reaction time is 0.5h~12h.
[0017] In a fifth aspect of the invention, an application of the dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material as described in the third aspect above is provided in circularly polarized luminescent materials, wherein the composite material serves as a circularly polarized luminescent active layer for information encryption storage, three-dimensional display, chiral sensing, or optoelectronic devices.
[0018] Preferably, the composite material achieves dynamic regulation of chiral optical signals under external stimuli, including one or more of temperature, solvent polarity, and surfactants.
[0019] In summary, compared with the prior art, the above-described technical solutions conceived by this invention mainly possess the following technical advantages: 1. The present invention constructs a dynamic chiral responsive luminescent conjugated polymer (claim 1) through molecular design, which for the first time covalently links the polyphenylene diethyne backbone with the chiral amino acid side groups, thus solving the problem at the molecular level that traditional chiral luminescent materials are difficult to balance chiral conformation stability and dynamic responsiveness in a single system. Specifically, the main chain is a rigid polyphenylene diacetylene backbone, which spontaneously folds into a stable single-handed helical conformation in aqueous solution due to hydrophobic effects. This avoids dependence on traditional self-assembly strategies and fundamentally avoids the inherent defect of luminescence efficiency loss caused by aggregation-induced emission quenching (ACQ). The chiral amino acid units on the side chains are covalently connected to the main chain. Their fixed chiral centers can effectively induce the entire main chain to form a partially chiral helix. The stability of the helical conformation is maintained through the dual synergy of intramolecular hydrogen bonding and π-π stacking, endowing the polymer with intrinsic and stable chiral optical activity and circularly polarized luminescence properties. Furthermore, the presence of carboxyl groups at the end of the side chains gives the polymer a negative charge on the surface, which not only endows the polymer with good water solubility but also provides a designable interface for subsequent electrostatic self-assembly with positively charged functional units, laying the molecular foundation for constructing chiral functional composite materials with tunable properties.
[0020] 2. This invention further combines the above-mentioned polyphenylene diacetylene-based folded body with gold nanoparticles through electrostatic self-assembly. The localized surface plasmon resonance (LSPR) effect of the gold nanoparticles synergistically enhances the polymer's luminescence performance, thereby breaking the traditional trade-off between high luminescence asymmetry factor and high luminescence quantum efficiency in chiral amplification strategies. The LSPR effect of gold nanoparticles can significantly enhance the excitation rate and radiative decay rate of neighboring fluorescent materials, allowing the composite material to retain the intrinsic chiral conformation of the polyphenylene diacetylene-based folded body and high gamma-ray emission efficiency. lum While increasing the value, its luminescence quantum efficiency is effectively compensated and improved, achieving high g in the same system. lum With Gao Φ PL To have both.
[0021] 3. The assembly state of the polymer-gold nanoparticle composite system of this invention can be dynamically controlled by external stimuli such as temperature, solvent polarity, and surfactants. Temperature can change the dissolution state of the cationic surfactant (CTAB), thereby controlling its electrostatic binding with the polymer, and thus synergistically inducing a reversible helical conformational change in the polymer backbone. Ultimately, this achieves dynamic, reversible, and wide-range control of circular dichroism signals and circularly polarized luminescence signals, overcoming the limitations of existing composite systems, which are mostly static structures and lack dynamic response capabilities. Attached Figure Description
[0022] Figure 1 This is a synthetic route diagram of the polyphenylene diethyne-based folded body as an example of the present invention.
[0023] Figure 2 The image shows the nuclear magnetic resonance spectrum of the polyphenylene diethyne-based folded body prepared in Example 1 of this invention.
[0024] Figure 3 The infrared spectrum of the polyphenylene diethyne-based folded body prepared in Example 1 of this invention is shown.
[0025] Figure 4 This is a gel permeation chromatography elution curve of the polyphenylene diacetylene folded body prepared in Example 1 of the present invention.
[0026] Figure 5 The images show the circular dichroism spectra of the polyphenylene diacetylene folded body prepared in Example 1 of this invention in aqueous solution and tetrahydrofuran solution, respectively.
[0027] Figure 6 The image shows the circularly polarized emission spectrum of the polyphenylene diethyne-based folded body prepared in Example 1 of this invention.
[0028] Figure 7 The circular dichroism spectrum shows the effect of adding hexadecyltrimethylammonium bromide on the conformation of the polymer (Poly-1) prepared in Example 1.
[0029] Figure 8 Fluorescence spectrum of hexadecyltrimethylammonium bromide (CTAB) blended with the polymer (Poly-1) prepared in Example 1.
[0030] Figure 9 This diagram illustrates the composite interaction of the polymer-gold nanoparticle composite system prepared in Example 1 and shows the response tests at different incubation temperatures; whereby... Figure 9(a) is a schematic diagram of the interaction between positively charged gold nanoparticles and negatively charged polyphenylene diacetylene folded bodies of Example 1 of the present invention; (b) is a circular dichroism (CD) spectrum of the composite system composed of the polymer and gold nanoparticles prepared in Example 1 at different incubation temperatures; (c) is a fluorescence spectrum of the composite system composed of the polymer and gold nanoparticles of Example 1 at different incubation temperatures.
[0031] Figure 10 The image shows the UV-Vis absorption spectrum of the gold nanoparticles prepared in Example 2.
[0032] Figure 11 The image shows the circular dichroism (CD) spectrum of the aqueous solution of the D-type polyphenylene diethyne-based folded body prepared in Example 3.
[0033] Figure 12 The CD spectra are those of gold nanoparticles and Poly-1 blended at different mass ratios.
[0034] Figure 13 The fluorescence spectra are those of gold nanoparticles and Poly-1 blended at different mass ratios. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0036] To achieve the above objectives, the following solutions are provided: In a first aspect of the invention, a dynamically chiral responsive luminescent conjugated polymer is provided. The repeating unit structure of the polymer is shown in Formula 1. The main chain is a polyphenylene diacetylene folded structure. In aqueous solution, the main chain has a helical conformation. The side chains contain chiral amino acid units. In Formula 1, the R group represents the side chain residue of the chiral amino acid unit. It is an L-type or D-type chiral carbon; Equation 1.
[0037] Preferably, R is one of methyl, isopropyl, isobutyl, sec-butyl, or benzyl.
[0038] Preferably, when R is methyl, the general formula of the repeating unit structure of the polymer is shown in Formula 2: Equation 2.
[0039] Preferably, the number-average molecular weight of the polymer is 3,000 to 50,000, and the molecular weight distribution is 1.10 to 2.0, thereby determining the number of repeating unit structures and the molecular weight distribution in the polymer.
[0040] In a second aspect of the present invention, a method for synthesizing the above-mentioned dynamically chiral responsive luminescent conjugated polymer is provided, comprising the following steps: (1) Amidation reaction of chiral amino acid esters with 3,5-diiodobenzoic acid was carried out in an organic solvent in the presence of an acid-binding agent and a condensing agent to obtain chiral monomer benzyl(3,5-diiodobenzoyl)-amino acid esters. (2) Under the protection of an inert gas, using palladium catalyst and copper salt as catalysts, the monomer obtained in step (1) is polymerized with m-diethynylbenzene via Sonogashira coupling reaction to obtain a polymer intermediate; (3) The polymer intermediate obtained in step (2) is subjected to alkaline hydrolysis to remove the benzyl protecting group, and the target polyphenylene diethynyl folded body is obtained, namely the dynamic chiral responsive luminescent conjugated polymer.
[0041] Preferably, in step (1), the chiral amino acid ester compound is a benzyl ester hydrochloride prepared from one of the following chiral amino acids: L-alanine, D-alanine, L-leucine, D-leucine, L-isoleucine, D-isoleucine, L-valine, D-valine, L-phenylalanine, D-phenylalanine; the acid-binding agent is triethylamine; the condensing agent is 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM); the organic solvent is tetrahydrofuran; the reaction temperature is room temperature, for example, 15℃~35℃, and the reaction time is 12h~48h; In step (2), the palladium catalyst is tetrakis(triphenylphosphine)palladium; the copper salt is cuprous iodide; the polymerization reaction is carried out in a mixture of organic solvent and triethylamine, the reaction temperature is 30℃~80℃, and the reaction time is 24h~72h; In step (3), the hydrolysis is alkaline hydrolysis, and the alkali used is sodium hydroxide or potassium hydroxide; the hydrolysis reaction is carried out in a mixed system of organic solvent and water, and the hydrolysis is purified by dialysis.
[0042] The following example illustrates the preparation of a specific dynamically chiral responsive luminescent conjugated polymer (such as the polymer represented by Formula 2), and the synthetic route is as follows: Figure 1 As shown, it includes the following steps: (1) Synthesis of chiral polyphenylene diethynyl folded polymer: L-alanine benzyl ester hydrochloride or D-alanine benzyl ester hydrochloride was subjected to an amidation reaction with 3,5-diiodobenzoic acid. Specifically, 1.0 g of 3,5-diiodobenzoic acid and 1.15 g of L-alanine benzyl ester hydrochloride were dissolved in a reaction flask containing 27 mL of tetrahydrofuran (THF), 1.8 mL of triethylamine (TEA) was added dropwise as an acid-binding agent, and then 1.48 g of 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM) was added as a condensing agent. The reaction was stirred at room temperature, and the reaction progress was monitored by thin-layer chromatography (TLC). The reaction time was approximately 24 h. After the reaction was complete, THF was removed by rotary evaporation, and 200 mL of ethyl acetate was added for extraction. The ethyl acetate layer was washed successively with 1 mol / L dilute hydrochloric acid, saturated NaHCO3 solution, and saturated NaCl solution. After drying with anhydrous Na2SO4, the mixture was filtered and concentrated by rotary evaporation. The crude product was purified by column chromatography using hexane / ethyl acetate (5 / 1, v / v) as eluent to obtain the chiral monomer benzyl(3,5-diiodobenzoyl)-propanoamino acid ester (labeled as 1a), as a white solid.
[0043] Under inert gas protection, the obtained monomer was polymerized with m-diethynylbenzene via a Sonogashira coupling reaction using palladium and copper salt as catalysts. Specifically, in a 50 mL reaction flask, 0.50 g of monomer 1a, 0.80 g of m-diethynylbenzene, 34 mg of tetrakis(triphenylphosphine)palladium (Pd(PPh3)4), and 8.60 mg of cuprous iodide (CuI) were added, and the mixture was purged with argon three times. 6 mL of TEA and 24 mL of ultra-dry N,N-dimethylformamide (DMF) were added to a pear-shaped flask, and after argon bubbling for 30 min, the mixture was injected into the reaction flask. The reaction was carried out at 40 °C, and the reaction was completed after approximately 43 h. The reaction solution was slowly added dropwise to methanol for precipitation, and the product was collected by centrifugation and vacuum dried at room temperature for 24 h to obtain a polymer intermediate (labeled Poly-1a), which was a light yellow solid.
[0044] The obtained polymer intermediate was subjected to alkaline hydrolysis to remove the benzyl protecting group. Specifically, 0.70 g of Poly-1a and 40 mL of DMF were added to a 250 mL reaction flask and stirred at 40 °C until completely dissolved. 0.46 g of NaOH was weighed and dissolved in 40 mL of distilled water, and the NaOH solution was gradually added dropwise to the reaction flask. The reaction was stirred at room temperature for 2 days. Dialysis was performed using a 5 kDa dialysis bag for 48 h, and the solution was concentrated by rotary evaporation, precipitated with acetone, centrifuged, and dried for 24 h to obtain the target polyphenylene diethynyl folded body (labeled Poly-1) with carboxyl groups on the side groups, which was a dark brown solid.
[0045] In a third aspect of the invention, a dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material is provided, comprising the polyphenylene diacetylene folded body prepared above and gold nanoparticles, wherein the polymer and gold nanoparticles are composited by electrostatic adsorption.
[0046] Preferably, the gold nanoparticles have a particle size of 5 nm to 100 nm; the surface of the gold nanoparticles is modified with a cationic surfactant, which is hexadecyltrimethylammonium bromide (CTAB) or hexadecyltrimethylammonium chloride (CTAC).
[0047] In a fourth aspect of the present invention, a method for preparing a dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material is provided, comprising the following steps: dissolving a polyphenylene diacetylene folded body in ultrapure water to prepare a polymer solution, mixing it with a gold nanoparticle dispersion with a positively charged surface in a certain proportion, utilizing the electrostatic adsorption between the negative charge on the polymer surface and the positive charge on the gold nanoparticle surface to graft polymer segments onto the surface of the gold nanoparticles, and centrifuging, washing, and drying to obtain the dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material.
[0048] The following example illustrates a method for preparing a dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material, comprising the following steps: Preparation of positively charged gold nanoparticles: Using tetrachloroauric acid (HAuCl4) as a raw material, gold nanoparticles are prepared by seed-mediated growth in the presence of the cationic surfactant hexadecyltrimethylammonium bromide (CTAB). First, a gold seed solution is prepared: 5 mL of 0.5 mM HAuCl4 solution and 5 mL of 0.2 M CTAB solution are mixed, and 0.6 mL of freshly prepared 0.01 M NaBH4 solution in ice water is added under vigorous stirring. The solution rapidly turns brownish-yellow. After stirring for another 2 min, it is allowed to stand at 25 °C for 2 h to obtain the gold seed solution. Subsequently, gold nanoparticles of different particle sizes are prepared: A certain amount of the gold seed solution is added to a growth solution containing HAuCl4, CTAB, and ascorbic acid. Taking the preparation of gold nanoparticles with a particle size of approximately 50 nm as an example, in 100 mL of growth solution, the concentrations were: 0.2 M CTAC, 25 mM HAuCl4, 40 mM ascorbic acid, and 1 mM potassium iodide. After adding an appropriate amount of seed solution, the mixture was allowed to grow at 30 °C for 15 min. After the reaction was complete, the mixture was centrifuged at 3600 rpm for 10 min to remove excess CTAC and unreacted substances from the supernatant. The resulting gold nanoparticles were then redispersed in a 1 mM CTAB aqueous solution for later use. Since CTAB is a cationic surfactant, the surface of the gold nanoparticles coated with it carries a positive charge. By adjusting the volume ratio of seed solution to growth solution, gold nanoparticles with a particle size range of 20-200 nm can be prepared. Preparation of electrostatic self-assembled composite materials: Poly-1, a poly(phenylene diacetylene) folded polymer, was dissolved in an aqueous solution to prepare a polymer solution. This solution was then mixed with a positively charged gold nanoparticle dispersion in a specific ratio. The polymer segments were grafted onto the gold nanoparticle surface using electrostatic adsorption between the negative charge on the polymer surface and the positive charge on the gold nanoparticle surface. Specifically, Poly-1 was dissolved in deionized water to prepare a polymer solution with a concentration of 1 mg / mL. 2 mL of the gold nanoparticle dispersion (approximately 1 mg / mL) was added dropwise to 1 mL of the polymer solution while stirring. The reaction was continued at room temperature for 4 hours. After the reaction was complete, the mixture was centrifuged at 5000 rpm for 5 minutes. The precipitate was washed three times with deionized water to remove unadsorbed polymer. The resulting product was redispersed in deionized water to obtain a dynamically chiral responsive luminescent conjugated polymer / gold nanoparticle composite material.
[0049] In this embodiment, the particle size of the gold nanoparticles is controlled by adjusting the ratio of seeds to growth solution. Gold nanoparticles of different sizes exhibit different localized surface plasmon resonance (LSPR) characteristic peaks, thereby enabling the control of the optical properties of the composite material. Furthermore, the grafting density of the polymer on the nanoparticle surface can be effectively controlled by adjusting at least one parameter among the initial polymer concentration, gold nanoparticle concentration, reaction time, and reaction temperature.
[0050] In a fifth aspect of the invention, an application is provided of a dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material in circularly polarized light-emitting devices, chiral sensing, smart displays, anti-counterfeiting encryption, or information storage.
[0051] Preferably, the composite material achieves dynamic regulation of chiral optical signals under external stimuli, including one or more of temperature, solvent polarity, ion type, or surfactant concentration.
[0052] By adjusting the temperature or the type / concentration of ions in the external environment, the assembly state of gold nanoparticles grafted with poly(phenylene diacetylene) folded bodies undergoes reversible changes. Temperature changes alter the aggregation state of surfactants, synergistically inducing chiral inversion of the polymer conformation, triggering a dynamic and reversible change in the helical conformation. Different types and concentrations of ions can effectively shield the electrostatic interactions between polymer segments, precisely controlling the spatial arrangement and co-assembly structure of negatively charged polymers on the surface of positively charged gold nanoparticles. The localized surface plasmon resonance (LSPR) effect of gold nanoparticles can effectively enhance the fluorescence emission of the polymer, enabling the composite material to possess both high luminescence asymmetry factor and high luminescence quantum efficiency. This achieves the controllable fabrication of intelligent nanomaterials integrating multiple responsiveness and strong circularly polarized luminescence, demonstrating significant application potential in fields such as dynamic optical anti-counterfeiting, multi-logic sensing, and high-density information storage.
[0053] Specifically, the aforementioned dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material simultaneously possesses the following multiple responsive properties: (1) Temperature response: CTAB in the system has a significant temperature response. This temperature-dependent binding behavior directly regulates the fluorescence emission intensity of the composite system. As a result, the fluorescence signal of the composite material of this application shows a significant increasing trend with the increase of incubation temperature in the range of 10℃ to 40℃. Under low temperature conditions (such as 10℃), the CTAB molecular chain collapses and the spatial configuration tends to be compact, and the binding effect with the polyphenylene diacetylene folded body Poly-1 is weak. As the incubation temperature increases (to 30℃ and 40℃), the CTAB molecular chain gradually extends, and the electrostatic binding effect between its positively charged ammonium head group and the carboxyl group of the Poly-1 side group is enhanced, resulting in an increase in the amount of CTAB bound to the Poly-1 chain.
[0054] (2) Ion response: Different types and concentrations of ions can shield the electrostatic interactions between polymer segments, altering the spatial arrangement and assembly structure of the polymer on the surface of gold nanoparticles. In aqueous solution, the composite material of this application, with CTAB as a cationic surfactant, exhibits a significant influence on the circular dichroism (CD) signal of the system based on its binding ratio with Poly-1: when the mass ratio of CTAB to Poly-1 is 0.14:1, the CD signal undergoes chiral reversal; when the mass ratio is 0.38:1, the CD signal is enhanced by approximately 11 times; and when the mass ratio increases to 0.56:1, the CD signal begins to weaken. This mechanism endows the composite material with the ability to dynamically, reversibly, and over a wide range of control over the CD signal and circularly polarized emission (CPL) signal.
[0055] (3) Solvent polarity response: The composite material of this application exhibits significant solvent polarity response in aqueous solution and tetrahydrofuran (THF), and its helical conformation changes with solvent polarity. In the good solvent THF, the π-π stacking interaction between phenylene diene groups is weak, and Poly-1 exhibits a relatively loose helical conformation; while in aqueous solution, hydrophobic interaction promotes a significant enhancement of the π-π stacking interaction of the main chain, exhibiting a more compact and stable helical conformation.
[0056] The technical effects of the present invention will be further illustrated below with reference to embodiments and comparative examples.
[0057] Example 1: This embodiment provides a method for preparing a dynamic chiral responsive luminescent conjugated polymer / gold nanoparticle composite material, including the following steps.
[0058] (1) Synthesis of chiral polyphenylene diethynyl folded poly-1: 1.0 g of 3,5-diiodobenzoic acid and 1.15 g of L-alanine benzyl ester hydrochloride were dissolved in a reaction flask containing 27 mL of THF. 1.8 mL of TEA was added dropwise, followed by 1.48 g of DMT-MM. The mixture was stirred at room temperature for 24 h. TLC monitoring showed the reaction was complete. THF was removed by rotary evaporation, and the mixture was extracted with 200 mL of ethyl acetate. The ethyl acetate layer was washed successively with 1 mol / L dilute hydrochloric acid, saturated NaHCO3 solution, and saturated NaCl solution. After drying with anhydrous Na2SO4, the mixture was filtered and concentrated by rotary evaporation. Column chromatography purification was performed using n-hexane / ethyl acetate (5 / 1, v / v) as eluent to obtain chiral monomer 1a as a white solid, yielding 0.86 g (86.2%).
[0059] In a 50 mL reaction flask, 0.50 g of monomer 1a, 0.80 g of m-diethynylbenzene, 34 mg of Pd(PPh3)4, and 8.60 mg of CuI were added, and the mixture was purged with argon three times under vacuum. 6 mL of TEA and 24 mL of ultra-dry DMF were measured, bubbled with argon for 30 min, and then injected into the reaction flask. The reaction was carried out at 40 °C for 43 h. The reaction solution was slowly added dropwise to methanol to precipitate the product. The product was collected by centrifugation and dried under vacuum at room temperature for 24 h to obtain polymer intermediate Poly-1a, a light yellow solid with a yield of 0.80 g and a yield of 87.9%.
[0060] 0.70 g of Poly-1a and 40 mL of DMF were added to a 250 mL reaction flask and stirred at 40 °C until completely dissolved. 0.46 g of NaOH was dissolved in 40 mL of distilled water and added dropwise to the reaction flask. The mixture was stirred at room temperature for 2 days. The solution was dialyzed through a 5 kDa dialysis bag for 48 h, concentrated by rotary evaporation, precipitated with acetone, and dried by centrifugation for 24 h to obtain the target polyphenylene diethynyl folded poly-1, a dark brown solid with a yield of 0.40 g (70.2%).
[0061] (2) Preparation of positively charged gold nanoparticles: Take a clean 25mL glass bottle, weigh 0.32g of CTAB and dissolve it in 9.75mL of ultrapure water. Mix the solution magnetically at 30℃ and 1000rpm. Then add 0.25mL of 10mM HAuCl4 aqueous solution. Then, under magnetic stirring, quickly inject 0.45mL of freshly prepared 20mM sodium borohydride ice water solution into the mixture. The solution color immediately changes from pale yellow to light brown. After stirring vigorously for 2 minutes, stop stirring and let it stand open in a 30℃ water bath for 1 hour to obtain the gold nanosphere seed solution. To prepare 50nm gold nanoparticles, first prepare two sample bottles, A and B, containing solutions of the same composition, and place both sample bottles in a 30℃ water bath. The specific synthesis steps are as follows: Add 5 mL of 0.2 M CTAC solution, 4.595 mL of H₂O, 100 μL of 25 mM HAuCl₄ solution, and 30 μL of 1 mM KI solution sequentially to two sample vials. Then add 220 μL of 40 mM ascorbic acid (AA) solution to each vial, and gently mix for 30 seconds, at which point the solution color changes from pale yellow to colorless. Next, add 55 μL of spherical seed solution to the growth solution in vial A, and shake until the solution turns pale red (approximately 20 seconds). Finally, transfer 55 μL of the solution from vial A to vial B and mix thoroughly for approximately 30 seconds. Incubate the solution in vial B at 30°C for 15 minutes to allow nanoparticle growth. Note that the total volume of solution in each sample vial should be strictly controlled to 10.0 mL. Collect the product in vial B by centrifugation at 5000 rpm for 10 minutes and redisperse it in 1 mL of 1 mM CTAB solution for later use.
[0062] (3) Preparation of electrostatic self-assembled composite materials: Poly-1 was dissolved in deionized water to prepare a 1 mg / mL polymer solution. 1 mL of gold nanoparticle dispersion (approximately 1 mg / mL) was added dropwise to the 1 mg / mL polymer solution while stirring. The reaction was carried out at room temperature for 4 hours. After the reaction was complete, the mixture was centrifuged at 5000 rpm for 10 minutes. The precipitate was washed three times with deionized water and redispersed in deionized water to obtain a dynamic chiral responsive luminescent conjugated polymer / gold nanoparticle composite material.
[0063] All the raw materials listed in this invention, as well as the upper and lower limits and ranges of the raw materials and the upper and lower limits and ranges of the process parameters (such as temperature, time, etc.), can realize this invention. Examples are not listed one by one here.
[0064] Figure 2 The image shows the nuclear magnetic resonance spectrum of the polyphenylene diacetylene folded body prepared in Example 1. Figure 3 The image shows the Fourier transform infrared (FT-IR) spectrum of the polyphenylene diacetylene folded body prepared in Example 1. Figure 3 The appearance of characteristic absorption peaks in the spectrum further confirms the presence of specific functional groups in the polymer: ~3300 cm⁻¹ -1 The broad and strong absorption band at ~1650 cm⁻¹ confirms the presence of amide NH and the possible presence of hydroxyl groups. -1 The prominent overlap of the C=O stretching vibration and the C=C vibration of the benzene ring skeleton in the region clearly indicates the introduction of amide bonds and aromatic units. The characteristic peaks closely match the functional groups in the designed molecular structure, thus confirming the presence of these components. Figure 2 and Figure 3 This fully demonstrates the successful synthesis of the target polymer.
[0065] Figure 4 The gel permeation chromatography (GPC) elution curve of the poly(phenylene diacetylene) folded body prepared in Example 1 shows that when the reaction time is 6 h, the number average molecular weight of the obtained polymer (Poly-1) is 6.70 kDa and its molecular weight distribution index is 1.2, indicating that the polymer has a relatively uniform molecular weight distribution and the polymerization reaction is well controllable.
[0066] Figure 5The circular dichroism (CD) spectra of the polyphenylene diacetylenic folded polymer prepared in Example 1 in aqueous solution and tetrahydrofuran (THF) solution are shown. Poly-1 was dissolved in water and THF to prepare solutions of specific concentrations, and CD spectroscopy was performed at room temperature. The results showed that Poly-1 exhibited only a weak CD signal in THF, while in aqueous solution, Poly-1 exhibited a significant and characteristic CD signal. This result indicates that Poly-1 possesses hydrophilic side groups and a hydrophobic backbone. It is precisely due to this amphiphilic structural feature that Poly-1 spontaneously undergoes helical folding driven by the hydrophobic effect; simultaneously, the chiral amino acid units with fixed configurations on the side chains induce the polymer to form a partially helical conformation. Typically, intramolecular hydrogen bonding and π-π stacking interactions can maintain the partially helical conformation of the folded polymer. In THF, a good solvent, the π-π stacking interaction between phenylene diacetylene groups is weak, and Poly-1 exhibits a relatively loose helical conformation. However, in aqueous solution, the hydrophobic interaction significantly enhances the π-π stacking interaction of the main chain, ultimately forming a more compact and stable helical conformation, indicating that the composite material prepared in this invention has solvent responsiveness. Figure 6 The image shows the circularly polarized emission (CPL) spectrum of the poly(phenylene diacetylene) folded body prepared in Example 1. The emitted circularly polarized light signal was recorded by exciting the polymer aqueous solution at a wavelength of 280 nm using a CPL spectrometer. The test results show that the polymer aqueous solution exhibits a significant CPL response. This result indicates that Poly-1 can not only form a stable single-handed helical conformation in aqueous solution, but also successfully transfer this chiral structure to the excited state, with a luminescence asymmetry factor (|g... lum The quantum efficiency can reach 0.02, and the luminescence quantum efficiency is 0.0264, exhibiting circularly polarized luminescence characteristics.
[0067] Figure 7The circular dichroism (CD) spectrum shows the effect of adding the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) on the conformation of the polymer (Poly-1) solution in Example 1. The specific testing method was as follows: Poly-1 was dissolved in deionized water to prepare a polymer stock solution with a concentration of 1 mg / mL; a CTAB stock solution with a concentration of 1 mg / mL was also prepared; then, the CTAB solution and the Poly-1 solution were blended at different volume-to-mass ratios, followed by CD spectral analysis. The results showed that as the CTAB / polymer mass ratio increased, the CD signal intensity and peak shape of Poly-1 changed significantly. When the volume-to-mass ratio of CTAB to Poly-1 reached 0.14:1, the CD signal reversed (i.e., the positive Cotton effect changed to a negative Cotton effect), exhibiting a clear conformational inversion phenomenon. This result fully demonstrates that Poly-1 has excellent responsiveness to CTAB, and that CTAB can induce its helical conformational inversion. The fundamental reason lies in the fact that as positively charged CTAB is continuously added, the negatively charged polymer side chains bind more and more tightly to it through electrostatic interactions. This strong electrostatic adsorption may not only induce a tighter packing or conformational rearrangement of the polymer backbone, leading to polymer chain shrinkage and densification; more importantly, this CTAB-induced structural rearrangement, which alters the chiral center or the entire helical arrangement, is very likely the driving force behind the CD signal reversal. Correspondingly, Figure 8 The image shows the fluorescence spectrum of a blend of hexadecyltrimethylammonium bromide (CTAB) and the polymer (Poly-1) from Example 1. The testing method was the same as above. The results show that at low concentrations of CTAB, CTAB significantly enhances the fluorescence emission intensity of Poly-1, accompanied by a noticeable blue shift of the emission peak. This may be due to electrostatic binding suppressing non-radiative transitions between the main chains. However, when the volume-to-mass ratio of CTAB:Poly-1 is greater than 0.56:1, the fluorescence intensity begins to decrease. This is because the addition of excessive CTAB may cause excessive aggregation of the polymer chains, or the structural characteristics of CTAB itself may lead to a certain degree of quenching effect on the polymer chains. Figure 7 and Figure 8 It can be seen that in the composite material system of Example 1, when the mass ratio of CTAB to polyphenylene diacetylene folded body is 2.26:1, the fluorescence emission intensity of the composite system reaches its maximum value, corresponding to its ion response characteristics.
[0068] Figure 9Image (a) shows a schematic diagram of the interaction between positively charged gold nanoparticles (AuNPs) and the negatively charged poly(phenylene diacetylene) folded body (Poly-1) from Example 1, and the preparation process of the composite material. The specific preparation and testing methods were as follows: Poly-1 was dissolved in deionized water to prepare a polymer solution with a concentration of 1 mg / mL. 1 mL of the gold nanoparticle dispersion (approximately 1 mg / mL) was added dropwise to 1 mL of the polymer solution (1 mg / mL) under continuous stirring, followed by stirring at room temperature for 4 h. After the reaction was complete, the mixture was centrifuged at 5000 rpm for 10 min, the precipitate was collected and washed three times with deionized water, and finally the precipitate was redispersed in deionized water to obtain the dynamic chiral responsive luminescent conjugated polymer / gold nanoparticle composite material. This result demonstrates that the negatively charged polymer and positively charged gold nanoparticles were successfully combined using electrostatic adsorption. The localized surface plasmon resonance (LSPR) effect of the gold nanoparticles can effectively enhance the luminescence performance of the composite system, laying the foundation for subsequent chiral optical signal enhancement.
[0069] Figure 9 Image (b) shows the circular dichroism (CD) spectra of the polymer-gold nanoparticle composite system prepared in Example 1 at different incubation temperatures. The specific testing procedure was as follows: the volume ratio of the Poly-1 solution to the gold nanoparticle dispersion was set to 1:1 (v / v), at which point the mass ratio of the polymer to the gold nanoparticles was exactly 1:1. After mixing and adding the mixture, the prepared composite system was incubated at different temperatures (10℃, 20℃, 30℃, 40℃) for 4 hours to obtain polymer-gold nanoparticle composite systems at different incubation temperatures, and their CD spectra were then tested. The test results showed that the Krafft temperature of CTAB in aqueous solution is approximately 25℃. This means that when the temperature is below 25℃ (e.g., 10℃), water is a poor solvent for CTAB, and CTAB tends to aggregate, making it difficult to effectively and uniformly adsorb onto the polymer surface; when the temperature is above 25℃ (e.g., 30℃, 40℃), water is a good solvent for CTAB, and CTAB micelles dissociate, allowing for more complete electrostatic binding with Poly-1. Analysis of the test results shows that during the modification process under 10℃ aqueous solution conditions, only a small portion of CTAB binds to Poly-1, while during the modification process under 30℃ aqueous solution conditions, due to the higher temperature than the Krafft temperature, most of the CTAB can bind to Poly-1. Therefore, by controlling the temperature, the dissolution state of CTAB can be altered, thereby controlling its adsorption amount on the polymer surface, ultimately achieving dynamic adjustment of the chiral optical signal of the composite material. Correspondingly, Figure 9Image (c) shows the fluorescence spectra of the polymer-gold nanoparticle composite system of Example 1 at different incubation temperatures. The testing method was the same as the CD test. The test results show that the fluorescence emission intensity of the composite material increases systematically as the incubation temperature increases from 10℃ to 40℃. This phenomenon confirms that temperature affects the amount of CTAB adsorption, and thus affects the coupling between the LSPR of the gold nanoparticles and the polymer. At 40℃, the amount of CTAB binding is the largest, resulting in the most sufficient interaction between the polymer and the gold nanoparticles, and the most obvious LSPR enhancement effect. Therefore, the composite system exhibits the strongest fluorescence emission performance at this temperature. Figure 9 As shown in (bc), in the composite material system of Example 1, as the incubation temperature increases from 10°C to 40°C, the CD signal and fluorescence emission intensity of the composite material both show an increasing trend, reaching the optimum at 40°C, indicating that temperature can effectively regulate the optical properties of the composite material.
[0070] Example 2: The difference between this embodiment and embodiment 1 is that: in step (2), different amounts of gold seed solution are used to prepare gold nanoparticles, and the particle size of the gold nanoparticles is controlled to be 30 nm.
[0071] Specifically, the amount of seed solution added to 10 mL of growth solution was increased to three times that of Example 1, and the mixture was allowed to grow at 30°C for 15 min. The remaining steps were the same as in Example 1, resulting in a composite material with gold nanoparticles having a particle size of approximately 30 nm. Figure 10 The image shows the UV-Vis absorption spectrum of the gold nanoparticles prepared in Example 2. The results show that the gold nanoparticles exhibit a distinct LSPR absorption peak at approximately 520 nm. Compared to the larger gold nanoparticles in Example 1 (approximately 538 nm), the absorption peak shows a significant blue shift, indicating a reduction in the particle size. This result confirms that the particle size of gold nanoparticles can be effectively controlled by adjusting the ratio of seeds to growth solution. Gold nanoparticles of different sizes exhibit different LSPR characteristic peaks, thereby enabling the regulation of the optical properties of the composite material.
[0072] Example 3: The difference between this embodiment and Example 1 is that in step (1), D-alanine benzyl ester hydrochloride is used instead of L-alanine benzyl ester hydrochloride for amidation reaction to obtain polyphenylene diethynyl folded body with opposite chiral configuration.
[0073] Specifically, 1.0 g of 3,5-diiodobenzoic acid and 1.15 g of D-alanine benzyl ester hydrochloride were reacted according to the same method as in Example 1, with the remaining steps being the same as in Example 1, to obtain a D-type chiral polyphenylene diethyne folded body and the corresponding composite material.
[0074] Figure 11 The image shows the circular dichroism (CD) spectrum of the aqueous solution of the D-type polyphenylene diacetylene folded body prepared in Example 3. The test results show that the D-type folded body exhibits a CD signal that is mirror-symmetrical to the L-type folded body in Example 1, indicating that it has an opposite chiral configuration. This result confirms that the chiral configuration of the polyphenylene diacetylene folded body can be precisely reversed by simply replacing the chiral amino acid unit (using D-alanine benzyl ester hydrochloride instead of L-alanine benzyl ester hydrochloride). Combined with the results of Example 1, it can be seen that folded bodies with different chiral configurations can impart corresponding chiral optical properties to the composite material after being combined with gold nanoparticles, indicating that the composite material system has universality in chiral configuration, and the direction of the circular dichroism signal can be controllably adjusted by selecting chiral units with different configurations.
[0075] Example 4: The difference between this embodiment and Example 1 is that the mixing ratio of Poly-1 solution and gold nanoparticle dispersion in step (3) is 1:1 (v / v), and the mass ratio of polymer to gold nanoparticles is 1:2.
[0076] Specifically, 1 mL of gold nanoparticle dispersion (approximately 1 mg / mL) was taken and added dropwise to 2 mL of polymer solution (1 mg / mL) while stirring. The mixture was stirred at room temperature for 4 hours. The remaining steps were the same as in Example 1.
[0077] Figure 12 and Figure 13The CD and fluorescence spectra of gold nanoparticles blended with Poly-1 at different mass ratios are shown. CD testing results indicate that the composite material still exhibits a significant CD signal, confirming that even with changes in the polymer-to-gold nanoparticle ratio, the helical conformation of Poly-1 is maintained, and the chiral optical signal can be effectively transferred to the composite system. Fluorescence testing results show that when the polymer-to-gold nanoparticle mass ratio is 1:2, the fluorescence emission intensity of the composite system is significantly enhanced compared to the pure polymer. This is attributed to the LSPR effect of the gold nanoparticles enhancing the polymer's luminescence. Further analysis of the test results from Example 1 (mass ratio 1:1) and the comparative example (pure polymer) reveals that the chiral optical properties of Poly-1 mainly originate from the chiral amino acid units attached to its side groups. As long as the side groups contain chiral amino acid units, the polymer and its gold nanoparticle composite material can acquire the corresponding CD signal characteristic structure. By combining Poly-1 with gold nanoparticles via electrostatic adsorption, the composite material retains the intrinsic chiral conformation of Poly-1 while significantly improving its fluorescence performance. Comparison of fluorescence enhancement effects under different composite ratios revealed that the fluorescence enhancement effect was most significant when the mass ratio of polymer to gold nanoparticles was 1:1. While the enhancement effect was still present when the mass ratio was adjusted to 1:2, the degree of enhancement decreased, indicating that there is an optimal range for the amount of gold nanoparticles to enhance the LSPR effect.
[0078] The results of Examples 1 and 4 show that the fluorescence emission performance of the composite material can be effectively adjusted by controlling the composite ratio of polymer and gold nanoparticles. Moreover, the chiral conformation of the material can remain stable under different composite ratios, which fully demonstrates that the composite material system has good structural stability and performance tunability.
[0079] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A dynamic chiral responsive luminescent conjugated polymer, characterized in that, The repeating unit structure of the polymer is shown in Formula 1. The main chain is a polyphenylene diacetylenic folded structure. In aqueous solution, the main chain has a helical conformation. The side chains contain chiral amino acid units. In Formula 1, the R group represents the side chain residue of the chiral amino acid unit. It is an L-type or D-type chiral carbon; Equation 1.
2. The dynamically chiral responsive luminescent conjugated polymer according to claim 1, characterized in that, R is one of methyl, isopropyl, isobutyl, sec-butyl, or benzyl.
3. The dynamically chiral responsive luminescent conjugated polymer according to claim 1, characterized in that, The polymer has a number-average molecular weight of 3,000 to 50,000 and a molecular weight distribution of 1.1 to 2.
0.
4. A method for preparing the dynamically chiral responsive luminescent conjugated polymer as described in any one of claims 1-3, characterized in that, Includes the following steps: (1) Amidation reaction of chiral amino acid esters with 3,5-diiodobenzoic acid was carried out in an organic solvent in the presence of an acid-binding agent and a condensing agent to obtain chiral monomer benzyl(3,5-diiodobenzoyl)-amino acid esters. (2) Under the protection of an inert gas, using palladium catalyst and copper salt as catalysts, the chiral monomer benzyl(3,5-diiodobenzoyl)-amino acid ester obtained in step (1) is polymerized with m-diethynylbenzene via Sonogashira coupling reaction to obtain a polymer intermediate. (3) The polymer intermediate obtained in step (2) is hydrolyzed to remove the benzyl protecting group, thereby obtaining the dynamic chiral responsive luminescent conjugated polymer.
5. The method for preparing the dynamically chiral responsive luminescent conjugated polymer according to claim 4, characterized in that, In step (1), the chiral amino acid ester compound is a benzyl ester hydrochloride prepared from one of the following chiral amino acids: L-alanine, D-alanine, L-leucine, D-leucine, L-isoleucine, D-isoleucine, L-valine, D-valine, L-phenylalanine, D-phenylalanine; the acid-binding agent is triethylamine; the condensing agent is 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMT-MM); the organic solvent is tetrahydrofuran; the reaction temperature is room temperature, and the reaction time is 12h to 48h. In step (2), the palladium catalyst is tetrakis(triphenylphosphine)palladium; the copper salt is cuprous iodide; the polymerization reaction is carried out in a mixture of organic solvent and triethylamine, the reaction temperature is 30℃~80℃, and the reaction time is 24h~72h; In step (3), the hydrolysis is alkaline hydrolysis, and the alkali used is sodium hydroxide or potassium hydroxide; the hydrolysis reaction is carried out in a mixed system of organic solvent and water, and the hydrolysis is purified by dialysis.
6. A dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material, characterized in that, The invention comprises the conjugated polymer and gold nanoparticles as described in any one of claims 1-3, wherein the polymer and the gold nanoparticles are combined through electrostatic adsorption.
7. The dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material according to claim 6, characterized in that, The mass ratio of the conjugated polymer to the gold nanoparticles is 0.06:1 to 5.08:1; the particle size of the gold nanoparticles is 5 nm to 100 nm; the surface of the gold nanoparticles is modified with a cationic surfactant, which is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.
8. A method for preparing the dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material as described in claim 6 or 7, characterized in that, Includes the following steps: The polyphenylene diacetylene folded body was dissolved in ultrapure water to prepare a polymer solution, which was then mixed with a gold nanoparticle dispersion with a positively charged surface in a certain proportion. The polymer chain segments were grafted onto the surface of the gold nanoparticles by utilizing the electrostatic adsorption between the negative charge on the polymer surface and the positive charge on the surface of the gold nanoparticles. After centrifugation, washing and drying, the dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material was obtained.
9. The application of the dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material according to claim 6 or 7 in circularly polarized luminescent materials, characterized in that, The composite material is used as a circularly polarized light-emitting active layer in information encryption storage, three-dimensional display, chiral sensing, or optoelectronic devices.
10. The application of the dynamic chiral responsive luminescent conjugated polymer / nanoparticle composite material according to claim 9 in circularly polarized luminescent materials, characterized in that, The composite material achieves dynamic regulation of chiral optical signals under external stimuli, including one or more of temperature, solvent polarity, or surfactant.
